PENYALURAN DANA ZAKAT PRODUKTIF MELALUI POLA PEMBIAYAAN (STUDI KASUS BMT BINAUL UMMAH BOGOR) - Erika Amelia (Signifikan: Jurnal Ilmu Ekonomi, 2012)
This article is going to analyze about the evaluation of Zakat Funds Distribution Pattern of Earning Through, Financing Atthe National Agency for Amil Zakat. Observations made by the author for about 4 months, both derived from surveys or direct interviews with parties BAZNAS and BMT Binaul BAZNAS Ummah as well as channel partners from the library or other reference materials. Based on data analysis research is that BAZNAS productive charity has granted funds in accordance with the principles of Islamic rule. The concept of financing as working capital revolving fund that is used by BAZNAS (in this case refers to BMT Binaul Ummah in the distribution) into a concept powerful enough to support the economic empowerment of the poor without a growing culture of consumerism. Because one major goal is to assist the distribution of alms mustahik economic conditions most of which are the poor. Financing revolving fund used by BAZNAS to channel aid funds sourced ZIS working capital for a number of traders and small entrepreneurs in Bogor.DOI: 10.15408/sjie.v1i2.2600